2020
DOI: 10.3390/healthcare8020164
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Motivation among Healthcare Workers in the East African Community between 2009–2019: A Systematic Review

Abstract: Healthcare workers are an essential element in the functionality of the health system. However, the health workforce impact on health systems tends to be overlooked. Countries within the Sub-Saharan region such as the six in the East African Community (EAC) have weak and sub-optimally functioning health systems. As countries globally aim to attain Universal Health Coverage and the Sustainable Development Goal 3, it is crucial that the significant role of the health workforce in this achievement is recognized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 56 publications
1
41
0
1
Order By: Relevance
“…In Nepal, it is a standard practice to give daily financial allowance to government workers for attending a course, whether on-site and away from base hospital. Likewise, performance-based financial incentives are used to enhance motivation and healthcare delivery by rural health-workers in general [ 23 ]. However, as these are not yet widely practiced for distance learning, provision of allowance may increase course recruitment and decrease program attrition rates.…”
Section: Challenges Of Distance-learningmentioning
confidence: 99%
“…In Nepal, it is a standard practice to give daily financial allowance to government workers for attending a course, whether on-site and away from base hospital. Likewise, performance-based financial incentives are used to enhance motivation and healthcare delivery by rural health-workers in general [ 23 ]. However, as these are not yet widely practiced for distance learning, provision of allowance may increase course recruitment and decrease program attrition rates.…”
Section: Challenges Of Distance-learningmentioning
confidence: 99%
“…First, the Government of Meru County could fund experimental design studies to develop and evaluate the cost-effectiveness of alternative interventions for healthcare professionals' motivation in the context of strengthening healthcare systems. Since the present study was conducted in a rural area that is relatively endowed with a good climate and fertile volcanic soils that are conducive to agriculture, the national government ought to consider sponsoring motivation studies in the semiarid and insecure counties to identify the motivation factors that could be used to attract and retain healthcare professionals in such challenging environments [5]. Such studies would yield a comprehensive nationwide understanding of factors influencing healthcare professionals' motivation.…”
Section: Areas For Future Studiesmentioning
confidence: 99%
“…Kenya is among the developing countries with suboptimally functioning healthcare systems [4]. One of the main challenges contributing to weak healthcare systems in developing countries is the critical shortage of skilled healthcare professionals, which is a significant demotivator [5]. The challenges that healthcare professionals continually face deplete their motivation to stay in the Kenyan health system, as evidenced by frequent strikes by these professionals [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative studies in the Kenya assessing healthcare workers’ happiness [ 14 ], health-related quality of life [ 15 ], and motivation [ 16 , 17 , 18 , 19 ] have also been published. In 2020, systematic reviews on healthcare workers happiness globally [ 20 ] and motivation in East Africa [ 21 ] were also published. These studies and reviews revealed an existing literature gap in healthcare workers’ experience of happiness, health, and motivation in the context of health systems, especially in the African region [ 15 , 16 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%